IMPLEMENTASI PROFIL PELAJAR PANCASILA TEMA KEWIRAUSAHAAN PADA MATA PELAJARAN EKONOMI DI SMA KRISTEN YPKPM AMBON - Istianah, Istianah; Picauly, Victry E; Manuhutu, Silvia (Atom : Jurnal Riset Mahasiswa, 2023)
The project to strengthen the profile of Pancasila students is a cross-disciplinary learning in observing and thinking of solutions to problems in the surrounding environment to enhance various competencies in the Pancasila Student Profile. This study aimed to analyze the Implementation of the Pancasila Student Profile on the Entrepreneurship Theme in the Subject of Economics at YPKPM Ambon Christian High School. The research method used was qualitative research with a phenomenological approach by conducting interviews with the economics teacher as a key informant and the head of the 5P Team as a supporting informant, which was carried out at YPKPM Ambon Christian High School; besides the data collected was also strengthened by documentation. The results showed that implementing the entrepreneurial theme of Pancasila student profiles included planning which consisted of the team formation stage, assessment, determining pieces/dimensions, creating modules, and conducting expos. Project implementation includes an introduction, context, planning, action, and reflection stages. The performance of this project must be distinct from the role of other parties. This project also has an impact, namely, the growth of Pancasila's character in students. The end of the project with the theme of entrepreneurship is the sale of student-processed products in school expo activities. The problems in the project implementation process did not hinder the project and could still be overcome.